Seletividade de herbicidas em mudas pré-brotadas de cana-de-açúcar - Dias, José Luiz Carvalho de Souza [UNESP] (2014)
The herbicides must provide selectivity to agricultural crops, moreover, they must control weeds without compromising crop's productivity. The aim was to evaluate the selectivity of herbicides applied on pre-emergence of weeds and pre-planting of three sugarcane cultivars planted by pre-sprouted seedlings (MPB) system. The experiment was carried out in the São Martinho Sugar Mill, in the municipality of Pradópolis (SP), under natural climatic conditions from September to November of 2013. The experimental design was a completely randomized with four replications. The treatments were arranged in a factorial (3x8), where the factor A consisted of three cultivars CTC14, CTC7 and RB966928; and the factor B consisted of seven herbicides: S-metolachlor (2640 g ha-1); clomazone (1000 g ha-1); sulfentrazone (800 g ha-1); diclosulam (200 g ha-1); metribuzin (1920 g ha-1); diuron + hexazinone (1170 + 330 g ha-1); S-metolachlor + sulfentrazone (2640 + 800 g ha-1) and a control without herbicide application. Visual symptoms of intoxication and stomatal conductance (gs) were evaluated at 14, 28, 35, 42, 49, 56 and 63 days after application (DAA); plant height and number of tillers at 14, 35, 49 and 63 DAA; the dry weight of shoot (DWS) and the dry weight of root (DWR) at 63 DAA. In the conditions which the experiment was conducted, the herbicides S-metolachlor, clomazone, metribuzin, diuron + hexazinone and S-metolachlor + sulfentrazone were selective to pre-sprouted seedlings of sugarcane. The herbicide diclosulam was the least selective one, followed by sulfentrazone. The CTC14 cultivar presented the lowest tolerance to the herbicides diclosulam and sulfentrazone